Dosimetric optimization of nuclear medicine therapy based on the Council Directive 2013/59/EURATOM and the Italian law N. 101/2020. Position paper and recommendations by the Italian National Associations of Medical Physics (AIFM) and Nuclear Medicine (AIMN). (September 2021) - Chiesa, Carlo; Strigari, Lidia; Pacilio, Massimiliano; Richetta, Elisa; Cannatà, Vittorio; Stasi, Michele; Marzola, Maria Cristina; Schillaci, Orazio; Bagni, Oreste; Maccauro, Marco
Highlights: Italian consensus about optimization in Nuclear Medicine Therapy. Optimization must deal with feasibility, limited resources and cost/benefit. Non-standardized therapies are defined, according to the variability of outcome. Supremacy of the radiation therapy legislation over the pharmacological laws. Appeal to EMA to obtain the official acknowledgment of this principle. Abstract: This recommendation by the Italian Associations of Nuclear Medicine (AIMN) and Medical Physics (AIFM) focuses on the dosimetric optimization of Nuclear Medicine Therapy (NMT) as clearly requested by the article 56 of the EURATOM Directive 2013/59 and its consequent implementation in article 158 in the Italian Law n. 101/2020. However, this statement must deal with scientific and methodological limits that still exist and, above all, with the currently available limited resources. This paper addresses these specific issues. It distinguishes among many possible kinds of NMT. For each type, dosimetric optimization is recommended or considered optional, according to the general criteria adopted in any human choice, i.e. a check of technical feasibility first, followed by a cost/benefit argument. The classification of therapies as standardized or non-standardized is presented. This is based on the complexity of the type of pathology, on the variability of the treatment outcome, and on the risks involved. According to the present document, which was officially delivered to Italian Health Ministry as necessary interpretation of the law, a therapeutic team can, in science and consciousness, overcome the indications of posology, to optimize and tailoring a treatment with dosimetry, on the basis of published national or international data or guidelines, without need of an Ethics Committee approval. Data collected in this way will provide additional evidence about optimal dosimetric reference values. As conclusion, a formal appeal is made to the European and National regulatory agencies for pharmaceuticals to obtain the official acknowledgment of this principle.